Pengembalian Bea Masuk atas Penetapan Pejabat Bea dan Cukai pada Kantor Pelayanan Utama Bea dan Cukai Tipe A Tanjung Priok - Nanang Kurniawan; Twenty Mariza Syafitri; Maya Novianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The activity of carrying out import activities of goods subject to service users is to carry out a self-assessment of customs notifications. The Customs and Excise Official determines the tariff and/or customs value upon notification, then informs the service user. Service users can submit objections or appeals to the placement of Customs and Excise Officials in the event of underpayment or overpayment. The purpose of this study is to determine the rate of return that has been made at the Type A Tanjung Priok Customs and Excise Service Office against the determination by Customs and Excise Officials. The data used are receipt reports and Payment Orders (SPM) for returns from 2017 - 2021 at the Main Service Office of Customs and Excise Type A Tanjung Priok. This research uses descriptive analysis. The results of the study show that the number of documents and the value of a cleaning is not directly proportional to the number of documents and the value returned. The increase or decrease in the number of document recoveries is not followed by an increase or decrease in the number of document returns. Whereas in the event of an increase or decrease in value by Customs and Excise Officials, the return of import duties to service users will also experience an increase or decrease